Performance of the regional inspectorate of North Sulawesi Province - Walangitan, Sendy Nita; Masengi, Evi Elvira; Mamonto, Fitri H. (Technium Social Sciences Journal, 2024)
The purpose of the study was to find out, analyze and describe the performance of the Regional Government Internal Supervisory Apparatus (APIP) in the Regional Inspectorate of North Sulawesi Province and the determinant factors. The method used in this research is qualitative research method. As for the results of the study, namely the effectiveness of the implementation of supervision is greatly influenced by coordination, planning, and object readiness in providing the necessary documents. Although there are standard work programs and tools, flexibility is still needed to adjust to conditions in the field. Challenges such as data delays are significant obstacles in achieving time efficiency and quality of supervision results. Understanding and carrying out supervisory tasks requires clear SOPs and official assignment letters. Coordination and communication with leaders and regional apparatus is essential to ensure readiness and smoothness of supervision. The main challenge arises from the lack of response and delays of regional apparatus in following up on inspections, which results in delayed and unplanned assignments. The implementation of supervisory tasks and functions is very important for coordination in the implementation of supervisory tasks to ensure consistency and uniformity in order to strengthen collaboration between the regional inspectorate and regional apparatus so that the inspectorate can synergize with related agencies and strengthen supervision. Education and Training of the existing Government Internal Supervisory Apparatus is felt to be lacking and limited due to the lack of budget allocations to participate in education or skills training. In fact, training and education are important to improve the quality of supervision and good government accountability.